Peranan religiositas terhadap pertimbangan profesional auditor - Ricky Bryan D. P. Tampubolon; Maria Fransisca (JAAF (Journal of Applied Accounting and Finance), 2023)
This study aims to examine the influence of task complexity, obedience pressure, and ethical perception on pertimbangan profesional, as well as to explore the role of religiosity as a moderator in the relationship between these variables. The sample used in this study consists of 37 senior and supervisory auditors in public accounting firms in Jakarta. The study uses a survey method with purposive sampling technique. The results show that task complexity has a significant positive effect on pertimbangan profesional, while obedience pressure has no significant effect, and ethical perception has a significant negative effect on pertimbangan profesional. Furthermore, task complexity, obedience pressure, and ethical perception simultaneously influence pertimbangan profesional. The study also shows that religiosity weakens the influence of task complexity on pertimbangan profesional, while strengthening the influence of obedience pressure on pertimbangan profesional. However, religiosity does not moderate the influence of ethical perception on pertimbangan profesional. This study provides an important contribution to public accounting firms and external auditors in developing professional training and development programs aimed at improving audit quality and addressing obedience pressure related to increasingly complex tax avoidance practices.